Differential diagnosis in otorhinolaryngology : symptoms, syndromes and interdisciplinary issues - Naumann, Hans Heinz (Georg Thieme, 1993)
This work is a comprehensive study on ENT differential diagnosis. Approximately 60 synoptic tables, organized according to principal symptoms in the head and neck region, present a ready survey of the diseases associated with each symptom and sign. Brief comments yield information on principal and collateral symptoms of the individual diseases, their pathogenesis, the necessary diagnostic steps and the alternatives disclosed by differential diagnosis. The book also features 133 additional tables which supply more data, and 66 schematic representations which are a help in arriving at the correct differential diagnosis.
Keywords: diagnostické techniky otologické; Diagnosis, Differential; otorinolaryngologie; diferenciální diagnóza; Diagnostic Techniques, Otological